COMPARATIVE ANALYSIS OF EASTERN SOURCES ON THE ISSUE OF THE PERIOD OF THE FORMATION OF THE MONGOLIAN EMPIRE - Ochilova D. J. (TARIXIY TADQIQOTLAR, 2026)
This article investigates the formation period of the Mongol Empire and the institutional foundations of its statehood, based on a comprehensive analysis of Eastern sources (Mongolian, Chinese, Persian, and Arabic). The research explores the stages of the empire’s transformation from nomadic traditions to a complex bureaucratic administrative apparatus, while identifying factographic variations across diverse civilizational sources. The author elucidates the peculiarities of imperial governance through the prism of political discourse and comparative source studies.